Incidence of colicinogenic strains among human Escherichia coli - Smarda, J; Obdrzálek, V (Journal of basic microbiology, 2001)
During the years 1993-1999, altogether 1,043 Escherichia coli strains from colons of different persons were screened for colicinogeny using a most susceptible procedure and indicator system. In control persons (with healthy colons), 41.37% producers of colicins were found. In patients suffering from salmonelloses, the proportion of colicinogenic Escherichia coli was the same. In patients with non-specific inflammatory colon diseases, the proportion of colicinogenic Escherichia coli strains appeared slightly though weakly, significantly or unsignificantly increased: to 47.50% in morbus Crohn and to 56.10% in colitis ulcerosa. These results suggest some sort of engagement of colicinogeny in the pathogenesis thereof. In malignant tumours of the colon, the incidence of colicinogenic Escherichia coli was not altered (40.58%). This does not indicate any colicin participation in the pathology of malignant tumours. In colitis ulcerosa, the incidence of colicinogenic Escherichia coli strains inhibiting Shigella sonei 17 (the indicator for colicin Js which generally inhibits interoinvasive strains of both species) increased from 21.94% (control samples) to 41.46%. Uropathogenic Escherichia coli strains shared the same incidence of colicinogeny as controls (42.08%), if they were not haemolytic; haemolytic ones were colicinogenic with only 22.37%. This difference was highly significant. The patterns of some colicin activities in the set of five indicator strains used suggested that several wild strains produced new, so far unknown types of colicins and/or combinations thereof.
Keywords: Colicins; mužské pohlaví; koliciny; ženské pohlaví; Escherichia coli; dospělí; incidence; Humans; Adult; Female; Incidence; lidé; Male